1991
DOI: 10.1113/jphysiol.1991.sp018701
|View full text |Cite
|
Sign up to set email alerts
|

ATP activates cationic currents and modulates the calcium current through GTP‐binding protein in rabbit portal vein.

Abstract: SUMMARY1. Effects of adenosine 5'-triphosphate (ATP) on ionic currents of dispersed smooth muscle cells of the rabbit portal vein were investigated using the voltageclamp procedure.2. ATP (> 300 ,M) produced transient and maintained inward currents. The former was inactivated within a few seconds, but the latter lasted more than several minutes. The transient but not the maintained current was blocked by pre-treatment with a,fl-methylene adenosine 5'-triphosphate (AMP-CPP). The amplitude of the latter was incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(22 citation statements)
references
References 32 publications
2
20
0
Order By: Relevance
“…The persistent enhancement of the Ca2" channel current and the lack of effect of desensitization by a,-methylene ATP suggest that this effect of ATP is not through purinoceptor stimulation, but probably through chelation of extracellular Mg2`(divalent cation block of Ca2" channel current carried by monovalent cations: Fukushima & Hagiwara, 1985). In rabbit portal vein, a similar phenomenon has been reported (Xiong et al, 1991). Figure 4 shows the effect of purinoceptor stimulation during a large depolarization.…”
Section: Resultssupporting
confidence: 51%
“…The persistent enhancement of the Ca2" channel current and the lack of effect of desensitization by a,-methylene ATP suggest that this effect of ATP is not through purinoceptor stimulation, but probably through chelation of extracellular Mg2`(divalent cation block of Ca2" channel current carried by monovalent cations: Fukushima & Hagiwara, 1985). In rabbit portal vein, a similar phenomenon has been reported (Xiong et al, 1991). Figure 4 shows the effect of purinoceptor stimulation during a large depolarization.…”
Section: Resultssupporting
confidence: 51%
“…ATP activates cation currents in the rabbit portal vein (Xiong et al, 1991;Pacaud et al, 1994), consistent with P2X receptor activation (Orre et al, 1996). The P2 receptor mediating contraction of the longitudinal muscle of the rat portal vein is also the P2X receptor subtype , and P2X 1 receptors have been identified on rat portal vein myocytes (Orre et al, 1996;Mironneau et al, 2001).…”
Section: Purinergic Signaling and Blood Vesselsmentioning
confidence: 89%
“…G proteins are known to modulate the activity of a number of ion channels (Clapham, 1994) and acetylcholine has been reported to open a cation channel in guinea-pig ileal smooth muscle (Inoue & Isenberg, 1990a;Komori et al, 1992) through a G protein-dependent mechanism. Intracellular dialysis of rabbit portal vein cells with the non-hydrolysable analogue of GDP, GDP-,B-S has been reported to reduce ATP-induced cation currents (Xiong et al, 1991), and Oike and colleagues (1993) reported that a pertussis toxin-sensitive G protein participated in the activation of a cation current by phorbol 12,13-dibutyrate, a protein kinase C activator. Further studies will be necessary to explore the possibility that G proteins also mediate the effects of AIL, 5-HT and ATP on channels in vascular smooth muscle cells.…”
Section: Discussionmentioning
confidence: 99%